Digital Self-Management Intervention Paths for Early Breast Cancer Patients: Results of a Pilot Study - Paula Poikonen-Saksela; Evangelos Karademas; Leena Vehmanen; Meri Utriainen; Haridimos Kondylakis; Konstadina Kourou; Georgios C. Manikis; Eleni Kolokotroni; Panagiotis Argyropaidas; Berta Sousa; Ruth Pat Horenczyk; Ketti Mazzocco; et al. (The Breast Journal)
Background. Despite excellent prognosis of early breast cancer, the patients face problems related to decreased quality of life and mental health. There is a need for easily available interventions targeting modifiable factors related to these problems. The aim of this study was to test the use of a new digital supportive intervention platform for early breast cancer patients. Material and Methods. Ninety-seven early breast cancer patients answered questions on wellbeing, exercise, and sociodemographic factors before systemic adjuvant treatment at the Helsinki University Hospital. Based on these answers and predictive algorithms for anxiety and depression, they were guided onto one or several digital intervention paths. Patients under 56 years of age were guided onto a nutrition path, those who exercised less than the current guideline recommendations onto an exercise path, and those at risk of mental health deterioration onto an empowerment path. Information on compliance was collected at 3 months on the amount of exercise and quality of life using EORTC-C30 scale, anxiety and depression using HADS scale at baseline and 12 months, and log-in information at 3 and 12 months. Results. Thirty-two patients followed the empowerment path, 43 the nutrition path, and 75 the exercise path. On a scale of 1–5, most of the participants (mean = 3.4; SD 0.815) found the interventions helpful and would have recommended testing and supportive interventions to their peers (mean = 3.70; SD 0.961). During the 10-week intervention period, the mean number of log-ins to the empowerment path was 3.69 (SD = 4.24); the nutrition path, 4.32 (SD = 2.891); and the exercise path, 8.33 (SD = 6.293). The higher number of log-ins to the empowerment (rho = 0.531, P=0.008, and n = 24) and exercise paths (rho = 0.330, P=0.01, and n = 59) was related to better global quality of life at one year. The number of log-ins correlated to the weekly amount of exercise in the exercise path (cc 0.740, P value <0.001, and n = 20). Conclusion. Patients’ attitudes towards the interventions were positive, but they used them far less than was recommended. A randomized trial would be needed to test the effect of interventions on patients’ QoL and mental health.